Photodegradation of Methylene Blue Using Carbon-Doped ZnSn(OH)6 Composite Coated on Membrane - Ernso Fenelon; Achmad Chusnun Ni’am; Truc-Mai Thi Nguyen; Ying-Fu Lin; Ya-Fen Wang; Sheng-Jie You (Journal of Chemistry)
The dye contamination of water is a global concern in the environment. In this study, the photocatalytic technology and membrane module were combined to improve the surface distribution of the active species of the catalyst for better degradation of the methylene blue (MB) dye under visible light. ZnSn(OH)6 was chosen due to carbon’s complex metal oxide doped to facilitate the application under visible light. The numerous characterizations were analyzed in the composites to verify the consistency of the optimum degradation of MB over the catalyst coated on the membrane. During the preparation of the ZnSn(OH)6 composite, the results confirmed that different reaction times and amounts of sodium hydroxide significantly affected the pollutant’s degradation. The carbon-doped composite denoted the largest surface area and increased the catalyst’s reactive sites on the membrane. The photocatalytic activity test showed that 1% carbon doped on ZnSn(OH)6 prepared at 160°C by hydrothermal method coated on the membrane had the optimal degradation of 89.74% of MB. This study contributes to the ongoing study and development of photocatalytic membranes for the photodegradation of wastewater treatment.